MUC5AC Expression in Various Tumor Types and Nonneoplastic Tissue: A Tissue Microarray Study on 10 399 Tissue Samples. (September 2021) - Rico, Sebastian Dwertmann; Mahnken, Moritz; Büscheck, Franziska; Dum, David; Luebke, Andreas M.; Kluth, Martina; Hube-Magg, Claudia; Hinsch, Andrea; Höflmayer, Doris; Möller-Koop, Christina; Fraune, Christoph; Möller, Katharina; et al.
Background: Mucin 5AC (MUC5AC) belongs to the glycoprotein family of secreted gel-forming mucins and is physiologically expressed in some epithelial cells. Studies have shown that MUC5AC is also expressed in several cancer types suggesting a potential utility for the distinction of tumor types and subtypes.Methods: To systematically determine MUC5AC expression in normal and cancerous tissues, a tissue microarray containing 10 399 samples from 111 different tumor types and subtypes as well as 608 samples of 76 different normal tissue types was analyzed by immunohistochemistry.Results: MUC5AC was expressed in normal mucus-producing cells of various organs. At least weak MUC5AC positivity was seen in 44 of 111 (40%) tumor entities. Of these 44 tumor entities, 28 included also tumors with strong positivity. MUC5AC immunostaining was most commonly seen in esophageal adenocarcinoma (72%), colon adenoma (62%), ductal adenocarcinoma of the pancreas (64%), mucinous carcinoma of the ovary (46%), diffuse gastric adenocarcinoma (44%), pancreatic ampullary adenocarcinoma (41%), intestinal gastric adenocarcinoma (39%), and bronchioloalveolar carcinoma (33%). Clinically relevant tumors with complete or almost complete absence of MUC5AC staining included small cell carcinoma of the lung (0% of 17), clear cell renal cell carcinoma (0% of 507), papillary thyroid carcinoma (0% of 359), breast cancer (2% of 1097), prostate cancer (2% of 228), soft tissue tumors (0.1% of 968), and hematological neoplasias (0% of 111).Conclusion: The highly standardized analysis of a broad range of cancers identified a ranking order of tumors according to their relative prevalence of MUC5AC expression.